A highly selective diarylethene chemosensor for dual channel recognition of CN− and Zn2+ and its application. Issue 17 (26th April 2019) - Gao, Wendan; Li, Hui; Zhang, Yaping; Pu, Shouzhi
Abstract: A novel diarylethene chemosensor comprising 3-aminobenzofuran-2-carboxamide Schiff base (1O ) was synthesized and the photophysical and sensing behaviors of1O were further investigated. Importantly, the introduction of electron-withdrawing group to1O made the sensor an efficient tool for detection of toxic cyanide even in the presence of other plausible interfering anions including fluoride and acetate. In particular, addition of CN − to1O visibly changes the color from colorless to orange-red, which can be observed by the naked eye. Apart from this, it also exhibited an outstanding fluorometric sensing toward Zn 2+ with high selectivity and sensitivity. Moreover, the remarkable spectral responses of the devised sensor prompted us to fabricate molecular logic circuit. Furthermore, the sensor was successfully applied to the detection of CN − on test strips and silica coated microslides, and the methods were very simple to operate without resorting to any spectroscopic instrumentation. In addition, the1O can also effectively detect CN − and Zn 2+ in actual water samples. Graphical abstract: Image 1